2011
DOI: 10.1016/j.rmed.2010.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Association between protozoa in sputum and asthma: A case-control study

Abstract: This case-control study demonstrates an association between flagellated protozoa in sputum and asthma. It is now necessary to confirm and characterise the protozoa using genetic techniques based on 18S ribosomal RNA. Once tis is established it would be worthwhile to determine if asthma symptoms improve when treated by anti-protozoal agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
2
12
0
1
Order By: Relevance
“…In a study in which the relationship between protozoa and asthma was evaluated [6], data supported the hypothesis that protozoa were more prevalent in patients diagnosed with asthma than in comparable controls. That study also investigated the relationship between presence of protozoa in sputum and dampness in the house and the data did not support the hypothesis that an increased prevalence of protozoa in sputum was associated with living in damp houses.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In a study in which the relationship between protozoa and asthma was evaluated [6], data supported the hypothesis that protozoa were more prevalent in patients diagnosed with asthma than in comparable controls. That study also investigated the relationship between presence of protozoa in sputum and dampness in the house and the data did not support the hypothesis that an increased prevalence of protozoa in sputum was associated with living in damp houses.…”
Section: Discussionmentioning
confidence: 81%
“…Lophomonas blattarum is another example of a single-cell eukaryote that occasionally appears to infect humans. Only a few articles reported that Lophomonas blattarum and other flagellated protozoa caused bronchopulmonary infections in humans [26]. No human cases of bronchopulmonary flagellated protozoa were reported from Turkey, but only a few cases were diagnosed as L. blattarum by Levent Doğancı (Bayındır Hospital, Turkey, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…In two previous studies reagents (e.g., saline, lab water, lab surfaces) have been analyzed to assess its influence on microbiota results from BAL (Bittinger et al, 2014; Krause et al, 2016); however, in other studies this was not done (Erb-Downward et al, 2011; van Woerden et al, 2011, 2013). Nevertheless, none of the studies investigating reagents showed that Candida abundance reached >50% as has been found in BAL samples from ICU patients (Krause et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Lower respiratory tract mycobiota were investigated in 30 asthma patients and compared to 13 controls (van Woerden et al, 2011, 2013). Patients were free of oral steroid use ≥2 weeks prior to induced sputum sampling but most of them were on inhaled corticosteroids.…”
Section: Mycobiome Of Patients With Asthma Bronchialementioning
confidence: 99%
“…It is possible that the organism exists as a commensal in some individuals and may only be pathogenic in the context of a causal web of aetiological factors [12]. It is also possible that more than one species is being observed which has similar features under light microscopy.…”
Section: Headingsmentioning
confidence: 99%